Experimental study of surface plasmon resonance enhancement using bimetallic film technique - Ong, Biow Hiem (2008)
The rapid civilization process of mankind, swift advancement in technology and surging human population have prompted mankind to be consistently conscious of their health, environment and surroundings. Increasing awareness and concerns have spearheaded many research and development activities in the area of optical sensors. Surface plasmon resonance (SPR), since it was first applied for gas and biosensing almost two decades ago, has made great strides in instrumentation development and sensing applications. In this thesis, SPR enhancement with the two-layer silver-gold metallic film technique is systematically investigated. Predominantly, this configuration integrates the better evanescent field enhancement of silver, the improved SNR of the SPR curve achievable with silver, and the high chemical resistance and biocompatibility of gold.